Pengaruh Gaya Kepemimpinan, Karakteristik Individu dan Motivasi Terhadap Kinerja Karyawan CV Adi Farm Mlonggo Jepara - Heni Pramudita; Lie Liana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of leadership style, individual characteristics and motivation on employee performance. The population in this study was 170 employees of CV Adi Farm Mlonggo Jepara. The sampling technique in this research used purposive sampling with the criteria of respondents being permanent employees who had a minimum work period of 1 year. The number of samples in this study was 80 respondents using Roscoe's theory. The data analyzed is primary data with data collection methods through questionnaires distributed to respondents. The data processing results obtained in this research include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, coefficient of determination tests (R²) and hypothesis tests. The results of this study show that leadership style has no effect on employee performance, individual characteristics have a negative and significant effect on employee performance and motivation has a positive and significant effect on employee performance.